(untitled) (RENOTE, 2022)
Comitê Técnico Adilson Vahldick - Universidade do Estado de Santa Catarina Alberto do Canto Filho - Universidade Federal do Rio Grande do Sul Alex Mazzuco - Universidade Federal do Rio Grande do Sul Alexandra Lorandi - Universidade Federal do Rio Grande do Sul Aliane Loureiro Krassmann - Instituto Federal Farroupilha Ana Marli Bulegon - Universidade Franciscana André Peres - Instituto Federal do Rio Grande do Sul - Campus Porto Alegre Andre Zanki Cordenonsi - Universidade Federal de Santa Maria Andreia Solange Bos - Universidade Federal Rio Grande do Sul Barbara Avila - Instituto Federal Farroupilha Breno Fabrício Terra Azevedo - Instituto Federal de Educação, Ciência e Tecnologia Fluminense Carine Loureiro - Instituto Federal Rio Grande do Sul Carla Barvinski - Universidade Federal da Grande Dourados Carla Berkenbrock - Universidade do Estado de Santa Catarina Cecilia Flores - Universidade Federal de Ciências da Saúde de Porto Alegre Cristina Mesquita - Polytechnic Institute of Bragança Cristina Pescador - Universidade de Caxias do Sul Daniel Lopes - Universidade Federal do Rio Grande do Sul Daniela Bagatini - Universidade Federal do Rio Grande do Sul/Universidade de Santa Cruz do Sul Débora Valletta - Universidade Federal do Rio Grande do Sul Elisa Boff - Universidade de Caxias do Sul Emanuel Queiroga - Universidade Federal de Pelotas Erico Amaral Universidade Federal do Pampa - Universidade Federal do Pampa Evandro Preuss - Universidade Federal do Rio Grande do Sul Fabiana Sgobbi - Universidade Federal do Rio Grande do Sul Fabrício Herpich - Universidade Federal do Rio Grande do Sul Felipe Becker Nunes - Antonio Meneghetti Faculdade Francieli Ludovico - Universidade Federal do Rio Grande do Sul Gabriela Perry - Universidade Federal do Rio Grande do Sul Giliane Bernardi - Universidade federal de Santa Maria Gilse Falkembach - Universidade Federal do Rio Grande do Sul Gleizer Voss - Instituto Federal Farroupilha Heli Meurer - Centro de Tecnologia da Informação e Comunicação do Estado do Rio Grande do Sul S.A. 0 Herik Rodrigues - Universidade Estadual do Piauí Janete Sander Costa - Universidade Federal do Rio Grande do Su Juarez Bento Silva - Universidade Federal de Santa Catarina Juliano Varella de Carvalho - Universidade Feevale Karen Cardoso - Universidade Federal do Rio Grande do Sul Kátia Rocha - Universidade Federal do Rio Grande do Sul Ketia Kellen da Silva - Universidade Federal do Rio Grande do Sul Larissa Monzon - Universidade Federal do Rio Grande do Sul Leticia Machado - Universidade Federal do Rio Grande do Sul Liane Margarida Rockenbach Tarouco - Universidade Federal do Rio Grande do Sul Maira Bernardi - Universidade Federal do Rio Grande do Sul Manuel Zunguze - Universidade Pedagógica de Maputo Marcelo Foohs - Universidade Federal do Rio Grande do Sul Marcelo Schmitt - Instituto Federal do Rio Grande do Sul - Campus Porto Alegre Marcia Notare - Universidade Federal do Rio Grande do Sul Marcio Bigolin - Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul (IFRS) - Campus Canoas Marco Trentin - Universidade de Passo Fundo Marcus Basso - Universidade Federal do Rio Grande do Sul Maria Lydia Fioravanti - Universidade de São Paulo Mariana Backes Nunes - Universidade Federal do Rio Grande do Sul Marilda Spindola - Universidade de Caxias do Sul Marlise Geller - Universidade Luterana do Brasil Míria Santanna dos Santos - Universidade Federal do Rio Grande do Sul Patrícia Campelo Costa Barcellos - Universidade Federal do Rio Grande do Sul Patrícia Scherer Bassani - Universidade Feevale Patrícia F. da Silva - Universidade Federal do Rio Grande do Sul Patricia Alejandra Behar - Universidade Federal do Rio Grande do Sul Patricia Estivalete - Universidade Federal do Rio Grande do Sul Pedro Henrique Dias Valle - Universidade Federal de Juiz de Fora Priscila Nicolete - Universidade Federal do Rio Grande do Sul Rodrigo Machado - Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul Rodrigo Silva - Universidade Federal do Rio Grande do Sul Rosane Aragón - Universidade Federal do Rio Grande do Sul Roseclea Medina - Universidade Federal de Santa Maria Rui Lopes - Polytechnic Institute of Braganca Sandra Assumpção Maria - Universidade Federal do Rio Grande do Sul Sílvio Cazella - Universidade Federal de Ciências da Saúde de Porto Alegre Silvia Bertagnolli - Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul Simone Oliveira - Universidade Federal do Rio Grande do Sul Taciana Pontual Falcão - Universidade Federal Rural de Pernambuco Taiser Barros PPGIE - Universidade Federal do Rio Grande do Sul Tiago Oliveira - Universidade Federal de São Paulo Valéria Costa - Fundação Oswaldo Cruz Vandoir Stormowski - Universidade Federal do Rio Grande do Sul Vinicius Hartmann Ferreira - Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul - Campus Feliz Viviane Backendorf - Universidade Federal do Rio Grande do Sul Coordenação Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Eliseo Reategui - UFRGS